Sepsis: a private hospital experience in Nepal - Lakhey, S.; Karki, B.; Shrestha, B.; Shakya, S.; Pandey, S.B. (Journal of Institute of Medicine Nepal, 2007)
Introduction: Sepsis, severe sepsis and septic shock are associated with high mortality. Data about patient profile and outcome of sepsis in ICU of Nepal is lacking. This study was conducted to investigate the source of infection leading to sepsis, its complications and eventual outcome. Material and Methods: It is a prospective study carried out from August 2004 to July 2005 in the ICU of B & B Hospital. The patients admitted in the ICU with the diagnosis of sepsis in accordance to the criteria laid down by American College of chest physician and Society of Critical Care Medicine were analysed and followed up. Age, sex, source of infection, duration of stay in the ICU, co-morbidities (Mc Cabe’s score), associated severe sepsis, septic shock, acute respiratory distress syndrome (ARDS), multiple organ dysfunction syndrome (MODS), disseminated intravascular coagulation (DIC) and the eventual outcome of sepsis were taken into account. The cause of death was also studied. Infection was diagnosed on the basis of clinical, radiological and microbiological parameters. Results: Of the 28 patients included in the study, 53.6% were male and 46.4% were female, the youngest was 15 years old and the oldest was 93 years old. More than half of the patients were more than 60 years old (53.6%) the average stay in the ICU was 6 days and the main source of infection was lung/respiratory tract (57.14%). 10.7% had sepsis, 89.3% had severe sepsis, 82% had septic shock, 42.9% had MODS, 32.1% had ARDS and 7.1% had DIC. The overall mortality was 39.3%. In elderly the mortality rate was higher (46.7%). The mortality rate was highest in patients with MODS. The mortality rate of sepsis, severe sepsis and septic shock increased progressively from 0%, 39.3% and 47.8% respectively. The mortality rate in patients with ARDS was 55.6%. The most commonly failing organ was circulatory system (82.1%). The mortality was 100% in patients with 3 or more organ failure. Conclusion: Sepsis with its complications has high mortality in our hospital that is similar to the recent findings in Brazil, Norway and USA. Awareness of sepsis and its appropriate treatment as per Surviving Sepsis Campaign Guidelines has become mandatory to reduce its mortality. Journal of Institute of Medicine Vol.28(1) 2006